The Effect of Capital Adequacy on Bank Profitability in Chinese Commercial Banks - Zhang, Qi (2022)
There is a debate over whether capital adequacy enhances or undermines bank profitability and past research has generated mixed findings. Meanwhile, although the significant roles of ownership structure variables in influencing bank profitability have been confirmed by past research, there is very limited knowledge regarding the moderating roles of ownership structure variables in the effect of capital adequacy on bank profitability. The present study examined the effect of capital adequacy on bank profitability as well as the moderating roles of four ownership structure variables, including state ownership, ownership concentration, managerial ownership, and institutional ownership. This study used fixed effects regression models to analyse the empirical data collected from 29 listed commercial banks in China over the 2011-2020 period, there are the following major findings. This study failed to identify any significant effect of capital adequacy on bank profitability. However, it was found that the effect of capital adequacy on bank profitability is positively moderated by state ownership, managerial ownership, and institutional ownership. In addition, ownership concentration was found to negatively moderate such effect when bank profitability is measured by ROA but not ROE. Based on this, the theoretical, practical, and policy implications of the above findings have been discussed at length in this dissertation.